MULTIVARIATE ANALYSIS AND WATER QUALITY INDEX ASSESSMENT OF RIVER ADOFI, SOUTH-SOUTH NIGERIA - Akawo, Nelson O.; Odita, G. N.; Nwaiku, F.; Azifuaku, J. N.; Igbeka, A. N. (FUDMA Journal of Sciences, 2025)
Water plays a vital role in ensuring food production, maintaining public health, promoting education, and fostering peaceful coexistence among citizens of any nation. The rapidly growing global population has made it essential to verify the quality of water sources before use. This study presents a multivariate analysis of the water quality status of Adofi River. Water samples were collected monthly (December 2020 to November 2021) from three stations along the river, selected based on human activities. The results showed that water temperature ranged from 26-30 ⁰C, water depth from 59.0 to 154.4 cm, Dissolved Oxygen (5.4 - 9.8 mg/L), Biochemical Oxygen Demand (2.0 – 8.0 mg/L), pH from 2.1 to 7.4, electrical conductivity from 102.0 to 132.4 µS/cm, acidity from 48.0 to 86.0 mg/L, alkalinity from 150.0 to 280.0 mg/L, Total Dissolved Solids from 80.0 to 135.0 mg/L, phosphate from 1.0 to 3.0 mg/L, sulphate from 20.4 to 52.0 mg/L, and nitrate from 14.5 to 26.4 mg/L. Sulphate, acidity, alkalinity, and water depth varied significantly (p < 0.05) between the stations. Principal Component Analysis revealed that PC1 accounted for 89.491% of the variation in the river's water quality. The scatter plot indicated a positive correlation of station 1 with TDS, water depth, BOD, pH, and D.O., station 2 with acidity, and station 3 with phosphate, nitrates, and water temperature. The water quality index results showed that water quality across the three stations ranged from poor to very poor, making it unfit for drinking purposes, and indicated disturbances...
Keywords: Adofi; River; Water quality index; ANOVA